Anaerobic co-digestion technology in solid wastes treatment for biomethane generation. Issue 5 (28th May 2017) - Al Mamun, Muhammad Rashed; Torii, Shuichi
Abstract : Anaerobic co-digestion is considered to be an efficient way of disposing solid wastes which can not only reduce environmental burden, but also produce bioenergy. Co-digestion of solid wastes in the absence of bacteria inoculums with variable mixing ratios of three wastes has been experimentally tested for 35 days digestion time to determine the biogas potential. The temperature remained relatively constant at a mesophilic range of 29–36°C throughout the study. An average pH of 7.4 was recorded from all digesters. The average biogas yields obtained from the four digesters (D1, D2, D3 and D4) were 13.31, 15.67, 16.52 and 19.12 L/day, respectively. The cumulative result showed that from co-digestion of D4 43.67%, 22.02% and 15.71% more biogas was produced, respectively, than others. The maximum and average COD reduction was 57% and 31%, respectively, in co-digestion wastes. The biogas comprised average of 61% CH4, 33.5% CO2, 222 ppm H2 S, and 4.7% H2 O, respectively.